Abraham Joshua Heschel and the sources of wonder - Marmur, Michael (Toronto ; Buffalo University of Toronto Press, 2016)
Abraham Joshua Heschel and the Sources of Wonder is the first book to demonstrate how Heschel's political, intellectual, and spiritual commitments were embedded in his reading of Jewish tradition.
Chapter One: Abraham Joshua Heschel, Heir and Pioneer -- Chapter Two: Heschel's Bible and the Hermeneutic of Surprise -- Chapter Three: A Living Response: Heschel and the Literature of the Sages -- Chapter Four: From Contemplation to Practice: Heschel's Two Maimonides -- Chapter Five: On the Verge of God: Heschel and Kabbalah -- Chapter Six: A New Accent: Heschel and Hasidism -- Chapter Seven: An Affinity of Strangers -- Chapter Eight: Heschel's Aspaklaria -- Chapter Nine: Heschel and the Call to Action.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 23, 2016).
Master record variable field(s) change: 072
Keywords: Heschel, Abraham Joshua, -- 1907-1972.; Heschel, Abraham Joshua, -- 1907-1972.; Judaism -- 20th century; Jewish philosophy -- 20th century; RELIGION -- Judaism -- General; Jewish philosophy; Judaism; PHILOSOPHY / Religious; 1900-1999; Electronic books